Media Sensation and Injustice on Domestic Violence and Incest in Motshabi Tyelele’s Shwele Bwawo! (A Grave Injustice)! - J. Adamu, Lydia; H. Thliza, John; V. Blamah, Titus (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Domestic violence and incest have become a recurring event in the lives of many girls and women in the world. Nigeria as a country, is no exception to these injustices met out on especially the feminine gender. The trend has left many in awe as to what the future holds for the affected female. Media reportage is a method that has presented issues and events to the audience thereby instigating the public to react positively or negatively to information. Reportage form has pushed people to react through backlashing such as: anger, protest and violence. The theory of feminism, which advocates for equality of both sexes is used to explicate the negative effect of media reportage on issues of domestic violence and incest. Motshabi Tyelele is a South African playwright who presents the play in this review as she explored her setting to present injustice of the justice system and media reportage. It is the crux of the matter as this paper intends to view Motshabi Tyelele’s Shwele Bawo! (A Grave Injustice!) in relation to media reportage of injustice on domestic violence and incest. The play advocates for equal treatment of persons irrespective of personality or social status. The play concludes by advocating objective investigative journalism.